Translation Analysis of Subtitle from English into Indonesian in Maleficent Movie - Yuli Kuswardani; Erike Septiani (Universitas PGRI Madiun, 2020)
This research aims at analysing subtitle in Maleficent movie. The research purposes are to analyze the clarity, accuracy and naturalness. Research approach is qualitative research. Research type is library research. Data are required from script of Maleficent movie, reader and experts‘ evaluation. This research uses documentation as data collecting technique. Researchers use investigator triangulation to make research can be trusted. Result of research shows: (1) clarity of subtitle is high with presentation of clear sentences is 77%, less clear sentence is 19.8% and unclear sentence is 3.2%; (2¬) accuracy of subtitle is high with presentation of accurate translation is 82.5%, less accurate is 14.5% and inaccurate translation is 3%; (3) naturalness of subtitle is high, with presentation of natural translation is 79.2% (1st expert) and 77.1% (2nd expert), less natural translation is 18.3 (1st expert) and 2.4 (2nd expert), and unnatural translaton is 22.3% (1st expert) and 1.6% (2nd expert)..